Basics of programming exercises using health and fitness technology in physical education pupils of secondary schools - M.V. Verkhovska (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : to present a framework for programming model classes using athletic health technologies at physical training lessons to pupils of general education schools. Material : the information base on research constitute official documents of the governing bodies of the European Union for the development of sports education. Also - the curricula and training programs for teachers of physical training, training programs on physical training of general educational institutions, research papers, reference and encyclopaedias, periodicals, national and foreign publications. The study involved 178 teachers of physical culture. Results : The general education schools were given the right choice of the existing options of training and education. Also - the construction of new ones. Therefore, the logical focus is physical education teachers to use technology in improving physical fitness physical training lessons, changing the concept of sports orientation of physical training on wellness. This concept aims at developing various curricula, development and testing of new technologies and more. Conclusions : Programming exercises using athletic health technologies do not change the logic of the training and educational process. They cancel stringent regulatory and authoritarian school programs, form the subject of a positive motivation to contribute to improving and training effect, adjust the health status of all participants.